Clinical and Pharmacological Approaches to the Prescription of Centrally Acting Antihypertensive Drugs for Uncontrolled Arterial Hypertension - A. V. Strygin; B. E. Tolkachev; A. O. Strygina; A. M. Dotsenko (Рациональная фармакотерапия в кардиологии, 2020)
Episodes of rapid increase in blood pressure due to uncontrolled arterial hypertension, previously known as a hypertensive urgency, is common clinical condition which many of practicing physicians are encountered daily. As a rule, these conditions are not life-threatening, however they could lead to target-organs damage if not promptly relieved. Therefore, clear evidence-based recommendations of optimal antihypertensive drug administration in these situations would provide more safe and effective therapy. Despite that, definite expert consensus regarding optimal choice of antihypertensive drugs to manage these patients have not been reached so far. The aim of the current review was to assess the results obtained from clinical trials regarding the safety and efficacy of moxonidine for urgent hypertensive therapy in patients with uncontrolled arterial hypertension admitted to emergency healthcare units as well as in those at the prehospital stage. Performed literature-based analysis revealed enough evidences proving that moxonidine can be administered in a single dose of 0.4 mg as a drug of choice in situations where prompt and stable hypotensive effect is desired. Results of comparative studies designed to closely match real clinical settings indicate that more adequate and sustainable therapeutic effect is achieved after moxonidine administration in comparison to other frequently used antihypertensive drugs.